2003
DOI: 10.1093/intimm/dxg108
|View full text |Cite
|
Sign up to set email alerts
|

TLR2 as an essential molecule for protective immunity against Toxoplasma gondii infection

Abstract: To investigate the role of the Toll-like receptor (TLR) family in host defense against Toxoplasma gondii, we infected TLR2-, TLR4- and MyD88-deficient mice with the avirulent cyst-forming Fukaya strain of T. gondii. All TLR2- and MyD88-deficient mice died within 8 days, whereas all TLR4-deficient and wild-type mice survived after i.p. infection with a high dose of T. gondii. Peritoneal macrophages from T. gondii-infected TLR2- and MyD88-deficient mice did not produce any detectable levels of NO. T. gondii load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
137
2
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(144 citation statements)
references
References 39 publications
3
137
2
2
Order By: Relevance
“…The critical role of TLR2 and TLR-linked cytoplasmic adapter protein, MyD88, against extracellular gram-positive bacteria has been shown in mice blood and kidney (4,36). Recently, we showed the importance of TLR2 (26) and MyD88 (7) for protective immunity to T. gondii infection. Consistent with these reports, the present study has demonstrated the renal dysfunction and histopathological damage following T. gondii infection in TLR2-deficient mice.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The critical role of TLR2 and TLR-linked cytoplasmic adapter protein, MyD88, against extracellular gram-positive bacteria has been shown in mice blood and kidney (4,36). Recently, we showed the importance of TLR2 (26) and MyD88 (7) for protective immunity to T. gondii infection. Consistent with these reports, the present study has demonstrated the renal dysfunction and histopathological damage following T. gondii infection in TLR2-deficient mice.…”
Section: Discussionmentioning
confidence: 98%
“…Renal inflammation markedly enhances synthesis of TLR2 and TLR4 mRNA in renal tubular epithelial cells (40). Recently, we revealed that MyD88 and TLR2 play a protective role against T. gondii infection (7,26).…”
mentioning
confidence: 99%
“…Glycophosphatidylinositol anchors and glycoinositolphospholipids from the protozoan parasite Trypanosoma cruzi (31), as well as lipopeptides/glycolipids from Mycoplasma spp (45) and Mycobacteria tuberculosis (46), have been shown to trigger inflammatory cytokine production by signaling via TLR2. Moreover, a role for TLR2 has been implicated in resistance to in vivo challenge with high numbers of oocysts from an avirulent strain of T. gondii (47). In addition to signaling in response to LPS, TLR4 has been implicated in the binding of ligands that are produced in response to cellular injury, such as murine heat shock protein 70 and components of the extracellular matrix (19).…”
Section: Discussionmentioning
confidence: 99%
“…Their ligands induce the production of inflammatory chemokines and cytokines (that is, CCL3, CCL5, interleukin (IL)-6, IL-8 and IL-12) that mediate recruitment of professional phagocytes and dendritic cells. [8][9][10] Crucial adaptative responses include CD8 þ cytotoxicity of infected cells, antibody-mediated phagocytosis and NK cell antibody-mediated cytotoxicity (NK-ADCC). A T helper 1 (Th1) profile (that is, IL-12 and interferon-g (IFN-g)) is essential to induce these mechanisms.…”
Section: Immune Response In Acquired Toxoplasmosismentioning
confidence: 99%